Population characterization of Steindachnerina insculpta (Fernández-Yépez, 1948) (Characiformes, Curimatidae) in the Piquiri river - DOI: 10.4025/actascibiolsci.v27i4.1269 - Holzbach, Arlei José (2008)
The objective of this work was to analyze the spatial and temporal distribution, to establish the relationship between weight and length, to analyze the reproductive development and to determine the length distribution from Steindachnerina insculpta, this specie is very important in the river for prey fishes. The fishes were obtained in 6 collections, from October 2002 to September 2003, in 3 sampling stations (Campina, Apertado, Altônia) , located in the Piquiri River, using gillnets with simple meshes of 2.4; 3; 4; 5 cm (between non adjacent knots). In this study we catched 226 individuals. The largest capture occurred in Campina station (217 individuals). The largest capture occurred on the day (D), and July presented the highest catch. The growth was negative allometric and the reproduction period was from September to January. Most of the individuals was among 9.5 and 10.0cm standard length